1973
DOI: 10.2224/sbp.1973.1.1.50
|View full text |Cite
|
Sign up to set email alerts
|

A Factorial Facet Analysis of Gough's Socialization Scale

Abstract: Five subscales were isolated by factor analysis from Gough and Peterson's (1952) socialization scale. Four of these scales showed improved statistical adequacy and increased theoretical yield when compared with several total scale versions. The 4 subscales were: family stability, behavioral control, relaxed security, and self-confidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0
1

Year Published

1977
1977
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 12 publications
1
7
0
1
Order By: Relevance
“…Our principal components analysis of the So scale replicated the factor structure identified previously in the literature using earlier versions of the So scale (Butt, 1973;Stein et al, 1966). The 46-item So scale yielded three interpretable factors: The Optimism subscale (reflecting selfconcept and trust/distrust); the Family subscale (reflecting features of the home/family life); and the Control subscale (reflecting behavioral control and conduct problems).…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Our principal components analysis of the So scale replicated the factor structure identified previously in the literature using earlier versions of the So scale (Butt, 1973;Stein et al, 1966). The 46-item So scale yielded three interpretable factors: The Optimism subscale (reflecting selfconcept and trust/distrust); the Family subscale (reflecting features of the home/family life); and the Control subscale (reflecting behavioral control and conduct problems).…”
Section: Discussionsupporting
confidence: 78%
“…The derived subscales were Optimism (a dimension of self-concept related to one's capacity for trust and optimism about the world), Family (a family/home environment dimension), and Control (a dimension of behavioral control). Scale names were adopted from previous research (Butt, 1973;Stein et al, 1966). Table 2 presents the means and standard deviations for the So scale, the So subscales, and the DBI for boys and girls.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Concernant les instruments réflexifs, les items de l'échelle du sentiment d'appartenance sont en partie dérivés de l'étude de Richer et Vallerand (1998). L'échelle de la socialisation a été partiellement inspirée de Butt (1973) et Gough (1960). Ces échelles sont souvent utilisées dans les études empiriques portant sur les réseaux.…”
Section: Méthodologie De La Rechercheunclassified
“…This may have lessened an interest in structure analysis of the So scale. Such analysis is essential, however, from a construct or a substantive point of view, and lately some studies have reported findings about the internal structure of the So scale (Butt, 1972(Butt, , 1973Stein, Gough, & Sarbin, 1966). The measurement model for the So scale is based on the assumption that the items relate linearly to the postulated trait.…”
mentioning
confidence: 99%